Diagnostic potential of 1‐step nucleic acid amplification assay in patients with head and neck squamous cell carcinoma based on CK19 expression in a primary lesion. (25th June 2015) - Suzuki, Masahiro; Matsuzuka, Takashi; Hashimoto, Yuko; Ikeda, Masakazu; Saijo, Satoshi; Omori, Koichi
ABSTRACT: Background: The purpose of this study was to investigate the effects of CK19 expression in the primary lesions of head and neck squamous cell carcinoma on the diagnosis of the cervical lymph node (CLN) metastasis using the 1‐step nucleic acid amplification assay. Methods: Primary lesions and 54 CLNs were resected from 21 patients with head and neck squamous cell carcinoma between 2009 and 2011. Each CLN was tested by the 1‐step nucleic acid amplification assay, and the CK19 mRNA copy number obtained was compared to the corresponding histopathological results. Results: In the primary lesion CK19‐positive group, the sensitivity and specificity of the 1‐step nucleic acid amplification assay against hematoxylin‐eosin staining were 86% and 100%, respectively. The p value by Fisher's exact test was < .0001, indicating statistical significance. Conclusion: These results suggest that 1‐step nucleic acid amplification offers similar diagnostic potential to that of histopathological diagnosis of CLN biopsy in patients with a CK19‐positive primary lesion. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E239–E245, 2016